Yuan Zhen’s New Music Bureau Poetry: Music and Ritual as Means of Governance - Tan, Mei Ah (Routledge Interdisciplinary Perspectives on Literature, 2025)
This book is the first comprehensive study of the twelve New Music Bureau poems by the influential poet-official Yuan Zhen 元稹 (779–831) in comparison with the response poems of Bai Juyi 白居易 (772–846). Its new perspective on music and ritual reveals connections between Yuan’s poems that otherwise appear to have no logical relation. While Bai’s poems are celebrated for their simple and direct style, those by Yuan are criticized for being abstruse and overloaded with historical and literary allusions. This study uncovers the inner mechanism of Yuan’s poems, his role in both the revival of Confucianism and the so-called “New Music Bureau Movement” in the Mid-Tang, his vision of the significance of music and ritual in securing lasting order after decades of military conflict and political upheaval, and his innovative use of New Music Bureau poetry as memorial.